Competitive Advantage of Geosmithia morbida in Low-Moisture Wood May Explain Historical Outbreaks of Thousand Cankers Disease and Predict the Future Fate of Juglans nigra Within Its Native Range - Williams, Geoffrey M.; Ginzel, Matthew D. (Frontiers in Forests and Global Change, 2021)
Bark beetles vector symbiotic fungi and the success of these mutualisms may be limited by competition from other microbes. The outcome of fungal competition is strongly influenced by the physical and chemical conditions of the wood they inhabit. These conditions are in turn subject to climatic variation. In particular, wood moisture content influences fungal competition, and therefore could help determine environmental suitability for thousand cankers disease (TCD) caused by Geosmithia morbida and its vector Pityophthorus juglandis. We conducted competition experiments in J. nigra wood that was naturally or artificially colonized by G. morbida and other fungi over a range of wood moisture content expected across prevailing U.S. climatic conditions. G. morbida outcompeted antagonistic fungi Clonostachys and Trichoderma spp. at < 5% equilibrium moisture content. Aspergillus spp. outcompeted G. morbida at low moisture in wood from Indiana. We fit a logistic regression model to results of the competition experiments to predict survival of G. morbida across the U.S. Expected survival of G. morbida was highest in historical TCD epicenters and accounted for the low incidence and severity of TCD in the eastern U.S. Our results also predict that under future climate scenarios, the area impacted by TCD will expand into the native range of J. nigra. Given its role in emergent forest health threats, climate change should be a key consideration in the assessment of risks to hardwood resources.